Self-Efficacy in Non-Exclusive Breastfeeding Mothers in North Tapanuli Regency - Elly Sianturi; Riance M Ujung (Postgraduate, University of Mataram, 2023)
Mother's milk (ASI) is the best food for babies, the composition of the nutrients contained in it is complete and easy for the body to absorb. In addition, breast milk components can provide immunity for the baby's body. The World Health Organization (WHO) recommends giving only breast milk, better known as exclusive breastfeeding, until the baby is six months old, and continued until the baby is 2 years old. The various benefits of breastfeeding that mothers and babies get do not necessarily have an impact on the percentage of mothers who breastfeed exclusively. According to data from the North Tapanuli District Health Service in 2021, the exclusive breastfeeding coverage rate was 58.9%. One of the positive factors in the success of exclusive breastfeeding is the self-efficacy of breastfeeding mothers. This research aims to analyze the self-efficacy of non-exclusive breastfeeding mothers. The research design was cross-sectional, with a total population of mothers who had babies aged 6-12 months who were non-exclusively breastfeeding and met the inclusion criteria. The results of the bivariate analysis showed that maternal occupation and type of delivery were not related to breastfeeding mothers' self-efficacy, while parity (p-value = 0.004 < 0.05) and breastfeeding problems (p-value = 0.021 < 0.05) were related to efficacy, breastfeeding mother herself. Multivariate analysis shows that parity has a significant influence on breastfeeding mothers' self-efficacy with a p-value = 0.014 < 0.05.